Smart campus: a user case study in Hong Kong. Issue 3 (4th September 2020) - Zhang, Yuchen; Dong, Zhao Yang; Yip, Christine; Swift, Sharon
Abstract : Smart campus, as a high‐end form of a smart education system and a mini‐scopic version of a smart city, has received increasing research and attention globally. The existing smart campus concepts are mostly technology‐driven, which simply introduces interconnection from a technological perspective to serve its residents but not necessarily adhering to the needs and interests of stakeholders in such a community. To fill this gap, this study presents a human‐centred approach for smart campus design and development, where a user case survey study is undertaken in Hong Kong primary and secondary schools. The overall aim of the survey is to accurately and timely capture and understand the perspectives of school stakeholders on education applications in the context of the smart campus. The findings from survey analysis are presented, with insights and suggestions for future smart campus development provided. The findings in this study are also expected to result in a benchmark reference of the smart campus concept for international educational providers, government, and technology companies that will deliver smart solutions.